2020
DOI: 10.1530/eje-19-0976
|View full text |Cite
|
Sign up to set email alerts
|

Carotid body chemosensitivity: early biomarker of dysmetabolism in humans

Abstract: Objective The carotid bodies (CBs) are peripheral chemoreceptor organs classically described as being O2 sensors, which are increasingly emerging as core players in metabolic control. Herein we evaluated CB activity in prediabetes patients and determined its correlation with dysmetabolism clinical features. Design and methods Prediabetes patients were recruited at the Cardiology Service, Hospital Santa Marta, Centro Hospitalar Lisboa Central, EPE (CHLC-EPE). The study was approved by CHLC-EPE and NOVA Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 43 publications
4
40
0
Order By: Relevance
“…It is widely known that increased sympathetic discharge is associated with chronic obstructive pulmonary disease, obstructive sleep apnea syndrome, cardiovascular diseases (hypertension, heart failure), renal pathologies, and metabolic disturbances (diabetes, obesity, metabolic syndrome). Increase in peripheral hypoxic chemosensitivity is a common mechanism stimulating sympathetic activation in the above conditions [4–9], but other stimulatory mechanisms are present.…”
Section: All Comorbidities Associated With Increased Morbidity/mortalmentioning
confidence: 99%
“…It is widely known that increased sympathetic discharge is associated with chronic obstructive pulmonary disease, obstructive sleep apnea syndrome, cardiovascular diseases (hypertension, heart failure), renal pathologies, and metabolic disturbances (diabetes, obesity, metabolic syndrome). Increase in peripheral hypoxic chemosensitivity is a common mechanism stimulating sympathetic activation in the above conditions [4–9], but other stimulatory mechanisms are present.…”
Section: All Comorbidities Associated With Increased Morbidity/mortalmentioning
confidence: 99%
“…Taking all these data together, we postulate that, in metabolic diseases, hyperinsulinemia, rather than hyperglycemia, is one of the major stimuli contributing to CB dysfunction [13,14] (Figure 2). Alongside these, increased CB chemosensitivity, measured by the Dejours test, observed in prediabetes patients is directly correlated with plasma insulin levels and with insulin resistance but not with fasting glycemia [21].…”
Section: Insulin: a Stimulus For Carotid Body Activation In Metabolicmentioning
confidence: 91%
“…Besides its role as an oxygen sensor, in the last few years, the CB has also been proposed to be a metabolic sensor implicated in the control of carbohydrate and lipid metabolism [ 8 , 9 , 10 , 11 ] and in the regulation of peripheral insulin sensitivity and glucose homeostasis [ 8 , 9 , 12 , 13 , 14 , 15 , 16 , 17 ] ( Figure 1 a). Recently, we showed that CB activity is increased in prediabetes and type 2 diabetes animal models [ 13 , 18 , 19 , 20 ] and patients [ 21 ] ( Figure 1 a) and that the abolishment of CB activity in animals, via chronic resection of the CSN or CB ablation, prevents and reverses dysmetabolism in rodent models of metabolic disease [ 13 , 15 , 16 ] ( Figure 1 b) by positively impacting glucose uptake and insulin signaling in the liver and in the visceral adipose tissue [ 15 ]. Additionally, we have previously shown that CSN resection in animal models prevents and restores the heightened sympathetic activity, measured as increased plasma and adrenal medulla catecholamines levels and increased LF bands and LF/HF ratio in heart rate variability analysis, which is characteristic of metabolic diseases [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CB is overactivated in prediabetic patients, and the variables related to CB chemosensitivity significantly correlate with fasting plasma insulin levels and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) [ 142 ]. Silencing CB activity via hyperbaric oxygen therapy significantly improved fasting blood glucose and glucose tolerance in patients with type 2 diabetes [ 143 ].…”
Section: Metabolic Syndrome and Cb Chemosensory Responsementioning
confidence: 99%